Idiopathic pigmented gingival fibromatosis: A case report - Tiwari, Abhishek Kumar; Shreedhar, Balasundari; Siddiqui, Attiuddin; Ghimire, Pratikshya (Indian Journal of Case Reports, 2021)
Gingival fibromatosis is a rare and heterogeneous group of disorders that develop as slowly progressive, local or diffuse enlargements within marginal and attached gingiva or interdental papilla. Gingival fibromatosis is a condition that can occur as an isolated disease or as a part of a syndrome or chromosomal abnormality. Here, we present the case of a 28-year-old male with pigmented gum enlargement in the maxilla and mandible. The clinical, radiographic, and histopathological features have been described in detail.